Engaging in entomophagy: The role of food neophobia and disgust between insect and non-insect eaters. (March 2023) - Sogari, Giovanni; Riccioli, Francesco; Moruzzo, Roberta; Menozzi, Davide; Tzompa Sosa, Daylan Amelia; Li, Jie; Liu, Aijun; Mancini, Simone
Highlights: Study on willingness to engage to entomophagy between insect and non-insect eaters. Lower Food Neophobia and Disgust for insect eaters than non-insect eaters. EAQ-Disgust is a more powerful predictor towards entomophagy than Food Neophobia. Abstract: Past tasting experience with edible insects could influence food neophobia (FN) and disgust, and consequently, it could increase the intention to engage with entomophagy by influencing our food neophobia and disgust. Thus, this study aims to measure the effect of food neophobia and insect disgust on the willingness to engage in entomophagy (WTE) and to explore the differences between consumers who had previous experience eating insects and those who did not. An online cross-sectional survey was distributed in five countries (Belgium, China, Italy, Mexico, and the USA) and the total sample (n = 3421) was divided into two consumer groups: insects eaters vs non-insect eaters. A Multigroup structural equation model was implemented to analyse the relationship between the FN and the sub-dimension Disgust of the Entomophagy Attitude Questionnaire-EAQ towards the WTE. The main results showed that FNS and Disgust negatively influence the WTE towards whole and processed insects. In particular, for the total sample, the effect of EAQ-Disgust is a more powerful predictor to explain the WTE for both wholes and processed insects than the FNS. However, interestingly, while the disgust dimension of the EAQ negatively influences the WTE with the same magnitude for both insect eaters and non-insect eaters, the FNS is related to the WTE with a stronger explanatory power for insect eaters than non-insect eaters. Thus, overcoming negative attitudes towards direct entomophagy, especially driven by disgust reactions through promoting tasting sessions is paramount to reducing disgust and legitimating insects as a food source.